ChemInform Abstract: Reductive Cyclization of Bromoenynamides with Alcohols as Hydride Source: Synthesis and Reactions of 2‐Amidodienes. Issue 19 (18th April 2013) - Greenaway, Rebecca L.; Campbell, Craig D.; Chapman, Helen A.; Anderson, Edward A.
Abstract Bromoenynamides undergo cyclization to cyclic amidodienes, representing the first example of a carbopalladation/reduction cyclization process which employs an alcohol as hydride source, proceeding via β‐hydride elimination from a palladium alkoxide.